Effects of Exogenous Corticosterone on Circulating Leukocytes of a Salamander (Ambystoma talpoideum) with Unusually Abundant Eosinophils. (4th March 2010) - Davis, Andrew K.; Maerz, John C.
Abstract : When animals become stressed, their levels of glucocorticoid hormones increase, causing white blood cells to move from tissues to circulation or vice versa. The primary alteration is an increase in the abundance of circulating neutrophils and a decrease in lymphocytes in circulation. A lesser-known effect is a decrease in the number of circulating eosinophils. Salamanders in the genus Ambystoma have unusually high numbers of circulating eosinophils, and as such, any effect of stress hormones on circulating leukocytes (especially eosinophils) of these species should be especially pronounced. We conducted an experiment to determine the effect of corticosterone administration on leukocyte counts (from blood smears) of A. talpoideum salamanders. Salamanders were captured and sampled as reference animals( n = 11 ), given a sham injection( n = 8 ), or injected with 0.1cc of a 100 μ g/mL corticosterone solution( n = 28 ) . After 24 hours, relative neutrophil counts were higher and relative lymphocyte counts lower, in the corticosterone group than the sham and control groups. Absolute counts showed that this effect was driven by a reduction in lymphocytes, since neutrophil counts were statistically similar across treatments. Importantly, relative and absolute numbers of eosinophils decreased in the sham and corticosterone groups, confirming the sensitivity of this cell to stress in amphibians.